Etnomatematıka Menara Kudus Sebagaı Sumber Belajar Bangun Datar Pada Jenjang Pendıdıkan Dasar - Nanang Nabhar Fakhri Auliya (Universitas Mathla'ul Anwar Banten, 2021)
The purpose of this study is to explore and explore the ethnomatematics of Menara Kudus building as a learning resource for flat-risers at the basic education level. The object of this research is the Menara Kudus building. This research method is to use the type of literature research using a qualitative approach in the form of a description. The results of this study indicate that in the part of the tower building, namely on the body, legs, and stairs of the tower there are several ornaments that can be modeled flat geometry including square, rectangle, equilateral triangle, right triangle, isosceles triangle, split. diamond and circle. The ethnomatematics of Menara Kudus can be applied in mathematics learning, namely by using the field trip method where students are invited directly to the Kudus Tower. Through observation activities, students identify the tower building related to the flat shape with the teacher's direction and students note the type of flat shape that is in the tower building. The teacher also gives assignments to students to be completed using various other learning resources.